COMPARATIVE ANALYSIS OF STANDARD TESTING METHODS FOR MEASURING FUELS & LUBRICANTS BIODEGRADATION - Boichenko, S.; Vovk, O.; Iakovlieva, A.; Kumeiko, S. (Science-based technologies, 2015)
Biodegradation in fresh water of materials such as plastics, lubricants, and other chemicals, which might end up in the environment after use, is of great importance. Therefore, certification of bio-based materials that may end up as waste in fresh water, with respect to their biodegradation behavior, is necessary. Standard testing methods for measuring biodegradation in fresh water are described in OECD guidelines, ASTM standards, ISO standards, etc. The most widely used testing methods for evaluating biodegradation of chemicals in aerobic aqueous medium are OECD 301 and OECD 310 for ready, and OECD 302 for inherent biodegradability, respectively. Similarly, the International standards ISO 7827, ISO 9408, ISO 9439, ISO 10707, ISO 10708, and ISO 14593 determine the biodegradability of organic compounds in an aerobic aqueous environment and are equivalent to OECD 301 and OECD 310. Test methods comparable to OECD 302 (inherent biodegradability) were also developed at ISO level (ISO 9887, ISO 9888). The American Standards ASTM D 5271 (plastics) and ASTM D 5864, ASTM D 6139 and ASTM D 6731 (lubricants) address the biodegradability of final products which are soluble, poorly soluble, or insoluble in water. Despite the availability of various testing methods for determining biodegradability in fresh water, further research is necessary for identifying the key factors affecting the accuracy and reproducibility of the results. Moreover, the corresponding specifications to characterize the biodegradability of bio-based complex materials in fresh water need to be further investigated.